Penentuan Harga Jual Khusus dengan Menggunakan Metode Full Costing (Studi Kasus pada Pabrik Tahu Sumberejo) - Heri Kuncoro Putro; Mukhammad Roni (Universitas Muhammadiyah Ponorogo, 2021)
he Full Costing method which is applied in accordance with cost accounting rules in calculating a product is sufficient to help reduce the occurrence of overcasting or undercoating caused by distortions of costing. The calculation of the cost of production using the Full Costing method should be carried out by a factory in determining the cost of production and determining the amount of the selling price. Production costs are cost elements that must be controlled as one of the bases in determining the selling price that is considered reasonable by consumers. In this study, the Pabrik Tahu Sumberejo has calculated production costs, but the calculations are not correct because they still use calculations with very simple methods. Calculations have not been carried out in detail, still not including some elements of the costs incurred during the production process. This study aims to determine the difference between the calculation of the cost of production carried out by the Pabrik Tahu Sumberejo so far with the calculation using the Full Costing method and its effect on the selling price. The results of the calculations in this study indicate that the calculation of the cost of goods manufactured using the Full Costing method compared to the cost of goods manufactured using the simple method gives different results. The calculation of the cost of production using the full costing method results in higher costs. This is because the calculations made by the factory are not correct in charging factory overhead costs for each product.